NLGN3 Upregulates Expression of ADAM10 to Promote the Cleavage of NLGN3 via Activating the LYN Pathway in Human Gliomas - Dang, Ning-Ning; Li, Xiao-Bing; Zhang, Mei; Han, Chen; Fan, Xiao-Yong; Huang, Shu-Hong (Frontiers in Cell and Developmental Biology, 2021)
The neuron derived synaptic adhesion molecular neuroligin-3 (NLGN3) plays an important role in glioma growth. While the role of autocrine NLGN3 in glioma has not been well-studied. The expression of NLGN3 in glioma was detected using immunohistochemistry. We further explored its function and regulatory mechanism in U251 and U87 cells with high expression of NLGN3. Knockdown of endogenous NLGN3 significantly reduced the proliferation, migration, and invasion of glioma cells and down-regulated the activity of the PI3K-AKT, ERK1/2, and LYN signaling pathways. In comparison, overexpression of NLGN3 yielded opposite results. Our results further demonstrate that LYN functions as a feedback mechanism to promote NLGN3 cleavage. This feedback regulation was achieved by upregulating the ADAM10 sheddase responsible for NLGN3 cleavage. Inhibition of ADAM10 suppressed the proliferation, migration, and invasion of glioma cells; oppositely, the expression of ADAM10 was correlated with a higher likelihood of lower grade glioma (LGG) in the brain. Our study demonstrate that glioma-derived NLGN3 promotes glioma progression by upregulating activity of LYN and ADAM10, which in turn promote NLGN3 cleavage to form a positive feedback loop. This pathway may open a potential therapeutic window for the treatment of human glioma.